INTERNATIONAL EXPERIENCE AND NATIONAL PRACTICE OF INTERNATIONAL CONFLICTS RESOLUTION IN AIRSPACE - Husar, Olga; Chulinda, Liudmyla (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to review incidents of conflict in airspace by analyzing international experience and provide specific examples of the practice of resolving international and national conflicts in airspace. Research methods: general scientific methods were used. The method of system analysis allowed to provide examples of real international conflicts in airspace and the practice of their settlement. The method of formal logic allowed to identify the factors influencing the emergence of international conflicts in airspace and to propose a mechanism for their resolution. Results: in order to resolve conflicts in airspace qualitatively, it is necessary to work on the development and implementation of advanced air traffic control systems, and the creation of international dispute resolution mechanisms. Discussion: the occurrence of airspace incidents is influenced by a number of factors: technological advances such as artificial intelligence and automation, unmanned aerial vehicles, advanced air traffic control systems; geopolitical processes; the level of the international community and effective mechanisms for resolving modern armed conflicts. The increasing use of unmanned aerial systems, commonly known as drones, presents both opportunities and challenges. Integrating UAVs into existing airspace management systems requires strict regulations, effective surveillance systems, and international cooperation to address airspace privacy and security concerns. The integration of artificial intelligence and automation into airspace management can improve conflict detection, resolution, and dialogue. The ability to control, protect, or deny the use of airspace can significantly affect the outcome and dynamics of conflicts, requiring careful management, diplomatic efforts, and compliance with international norms to ease tensions and promote peaceful resolution of disputes.